Women's movements and female board representation - Michael Neureiter; CB Bhattacharya (Business and Society Review, 2022)
Scholars know relatively little about the potential impact of women's movements on gender diversity in the corporate world. We aim to fill this gap in the literature by providing the first empirical analysis of the relationship between women's movements and female representation on boards of directors. Drawing on political process theory, we argue that the strength of a women's movement is positively associated with its ability to increase the number of women on corporate boards. Moreover, we posit that the effect of women's movements on female board representation is moderated by corporate opportunity structures, that is, attributes of firms that make them more or less receptive to social movement activities. Three firm characteristics are particularly relevant in the context of boardroom gender diversity: reputation-seeking behavior, commitment to corporate social responsibility, and political orientation. Using firm-fixed effects models to analyze data on more than 2000 companies from 10 countries over a period of 100.167emyears, we find support for three of our four hypotheses. Theoretical and practical implications are discussed.
Keywords: 330; corporate boards; female representation; gender diversity; political process theory; social movements; women's movement